Redefining global economic thinking for the welfare of society - Rahman, Md. Mashiur (Advances in finance, accounting, and economics (AFAE) book series., 2022)
"This book digs into the current climate of global wealth by examining some prevailing economic theories to uncover deficiencies of existing economic thinking and suggests guidelines for redefining the global economic atmosphere to create a world economy with more parity to the benefit of all of social"--